ASME/IEEE 2007 Joint Rail Conference and Internal Combustion Engine Division Spring Technical Conference 2007
DOI: 10.1115/jrc/ice2007-40096
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Derailments Due to Concrete Tie Rail Seat Deterioration

Abstract: Concrete tie rail seat abrasion/deterioration (RSA) has been an issue since the inception of concrete ties. As a result of recent derailments involving abraded concrete ties on curved track, the Federal Railroad Administration set up a task force to study abrasion/deterioration mechanisms and develop automated detection methods using existing research vehicles. A portion of this study reviews historical development of concrete abrasion due to moisture or foreign materials incorporated under the rail seat that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…In addition to research at UIUC, the John A. Volpe National Transportation Systems Center (hereafter referred to as "Volpe") modeled RSD to evaluate its consequences on track geometry. The work concluded that under high lateral loads, the rail could rotate, creating a pressure concentration at the field side which could exceed the crushing strength of the concrete [4].…”
Section: Rsd Failure Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to research at UIUC, the John A. Volpe National Transportation Systems Center (hereafter referred to as "Volpe") modeled RSD to evaluate its consequences on track geometry. The work concluded that under high lateral loads, the rail could rotate, creating a pressure concentration at the field side which could exceed the crushing strength of the concrete [4].…”
Section: Rsd Failure Mechanismsmentioning
confidence: 99%
“…According to a survey of North American Class I freight railroads conducted by researchers at the University of Illinois at Urbana-Champaign (UIUC), RSD was ranked as the most critical problem with concrete crossties and fastening systems [2]. RSD is defined as the loss of material from the concrete crosstie beneath the rail, and is exacerbated by the demanding loading environments in which concrete crossties are typically deployed [3,4]. RSD typically manifests as a triangular loss of material, with depth of wear increasing towards the field side of the rail seat ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…2 compressive strength of the concrete tie at the rail seat field side. In normal operation, compressive overloading (crushing) and repeated wheel loading produced stresses that initiated breakdown at the tie surface [2,3]. NUCARS simulations were conducted using measured track geometry taken prior to derailments to estimate the dynamic wheel loads.…”
Section: Figure 1: Rail Rollover In Curve Track Due To Consecutive Timentioning
confidence: 99%
“…The feasible mechanisms are abrasion, crushing, freeze-thaw cracking, hydraulic-pressure cracking, and hydro-abrasive erosion (Joh et al 2010;Zeman et al 2009). Of these mechanisms, hydraulic-pressure cracking and hydro-abrasive erosion were investigated at UIUC and found to be feasible mechanisms resulting in RSD (Zeman 2010;Choros et al 2007;Bakharev 1994). According to another study, RSD resembled damage that is typically caused by abrasion, with hydraulic-pressure cracking and freeze-thaw cracking also being identified as possible contributors (Bakharev 1994).…”
Section: Introductionmentioning
confidence: 99%